Lebanon Donors Conference--Paris III - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, remarked that Lebanon stands at a critical crossroad in the wake of the war in the previous summer. Lebanon now needs to go beyond reconstruction. He reviewed the implementation of the Lebanese Government’s economic and social reform program. The World Bank Group is providing financing support in three areas: first, the unprecedented step of providing grants from World Bank Group income for recovery and reconstruction. Second, the International Finance Corporation will provide 250 to 275 million dollars in financing for Lebanon’s financial and business community, including a guarantee program for small and medium-sized enterprises and a trade finance facility. Third, the Bank extended up to 700 million dollars in IBRD financing to support the implementation of the Government’s program, particularly its efforts to stimulate growth and to meet the needs of the poorest and most vulnerable elements of the population. The Bank is prepared to continue and intensify efforts in assisting the Government to implement its programs, to build institutional capacity, to improve procurement and financial management to undertake sector reforms, with a particular focus on those sectors such as power, which are key to the overall success of the program.The people of Lebanon have called on the world to help revive their economy. We have an opportunity to restore hope and stability that the Lebanese people and their children so deeply deserve.